PENGARUH CAR, LDR, DPK, NPL, BOPO, INFLASI, DAN SIZE TERHADAP PROFITABILITAS BANK (Studi pada Perusahaan Perbankan Umum yang terdaftar di Bursa Efek Indonesia Tahun 2015-2017) - HaulaRizqiMonadia, 14.05.62.0014; Badjuri, Achmad (Students' Journal of Accounting and Banking, 2018)
This study aims to examine and analyze the influence of Capital Adequacy (CAR),Loan to Deposit Ratio LDR, Third Party Funds (DPK), Non Performing Loans (NPL), Operational Costs and Operating Income ( BOPO), Inflation and Size against banking profitability (ROA) on the Indonesian Stock Exchange (IDX) for period of 2015-2017.The population of this research isa banking company. Samples are included in the criteria of this study were 87 financial Statements of banking companiesusing purposive sampling method. Methods of data analysis in this study using multiple linear regression analysis with SPSS 22 program.The results showed that the variables of LDR, DPK, and Sizesignificant positive effect onROA, while CAR, NPL, BOPO, Inflationhad a positive influence on ROA. Keywords:CAR, LDR, DPK, NPL, BOPO, Inflasi dan Size.